Ultrastructural study of the effects of tranexamic acid and urokinase on metastasis of Lewis lung carcinoma. - Tanaka, N. (Nature Publishing Group, 1982)
Lewis lung carcinoma cells were implanted in the foot-pads of mice and the effects of the plasminogen-plasmin inhibitor tranexamic acid (t-AMCHA) and of the plasminogen activator urokinase on metastasis were examined by electron microscopy. The intravascular tumour cells were not associated with thrombus formation in either control or urokinase-treated mice. Polymerized fibrin deposition around tumour cells and thrombi composed of fibrin and platelets was observed only in the mice given t-AMCHA. This suggests that the inhibition of fibrinolysis by tACC caused fibrin deposition and thrombus formation around intravascular tumour cells, which prevented release of the cells from primary foci to form secondary tumours. On the other hand, fibrinolysis induced by urokinase prevented thrombus formation, and accelerated cell release from primary foci. IMAGES: